The intermunicipal cooperation in the no-metropolitan areas - Endlich, Angela Maria (2018)
The intermunicipal cooperation, in its various institutional forms, grows numerically, in addition to incorporating diverse purposes. Changes in human spatiality require modifying command forms. We dedicated this paper to this theme. Shared management, though emphasized for metropolitan areas, is essential for other areas, polarized by smaller cities, as a way of making public services and equipment that are adequate to society. In addition, they contribute to a sufficient demand for obsolete structures. In addition, intermunicipal cooperation is an important form of political force composition among small localities, contributing to their visibility in the territorial planning. We combine quantitative methodological procedures with the purpose of apprehending the progress of these experiments, as well as qualitative procedures that allowed us to know in a deeper way their dynamics. The paper brings reflections about these forms of cooperation, signaling for their expansion in Brazil, the possible obstacles they encounter, as well as their spatial aspects.